2010
DOI: 10.1248/cpb.58.336
|View full text |Cite
|
Sign up to set email alerts
|

Polyprenylated Benzoylphloroglucinol-Type Derivatives Including Novel Cage Compounds from <i>Hypericum erectum</i>

Abstract: ]undecane skeletons arising from a polyprenylated phloroglucinol precursor by a transannular cyclization reaction. The isolated compounds were tested for suppressive activity, but they showed only weak activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 20 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…1 ). The structures of the known compounds were elucidated by comparing their NMR data with those reported in the literature, and they were identified as attenuatumione C ( 7 ) 24 , sampsonione K ( 8 ) 10 , otogirinin D ( 9 ) 25 , and sampsoniones M ( 10 ) 10 and N ( 11 ) 11 .…”
Section: Resultsmentioning
confidence: 99%
“…1 ). The structures of the known compounds were elucidated by comparing their NMR data with those reported in the literature, and they were identified as attenuatumione C ( 7 ) 24 , sampsonione K ( 8 ) 10 , otogirinin D ( 9 ) 25 , and sampsoniones M ( 10 ) 10 and N ( 11 ) 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Both types of substituents are susceptible to cyclization and oxidation processes resulting in bi-1,2 or tricyclic 3,4 molecules, as well as complex caged compounds. 5,6 The structural diversity among acylphloroglucinols leads to various pharmacological activities in vitro and in vivo. As reported by the Gibbons group, several representative members of this class of compounds display significant antibacterial activity especially against Gram-positive bacteria.…”
mentioning
confidence: 99%
“…The 1 H-NMR spectrum ( Table 1) Comparison of the 1 H-and 13 C-NMR data ( Table 1) of 1 with those of otogirinin B [11] indicated that their structures were closely related, except that the 14-lavandulyl group of 1 replaced a 14-geranyl group of otogirinin B [11]. This was supported by both HMBCs (Fig.…”
mentioning
confidence: 76%
“…Compound 1 showed similar CD Cotton effects (221 ([q] ¼ þ 1410) and 252 ([q] ¼ þ1049) nm) compared with those of the analogous benzoylphloroglucinol derivative otogirinin B[11]. Compound 1 showed similar CD Cotton effects (221 ([q] ¼ þ 1410) and 252 ([q] ¼ þ1049) nm) compared with those of the analogous benzoylphloroglucinol derivative otogirinin B[11].…”
mentioning
confidence: 99%